Caudal bupivacaine - midazolam for post operative analgesia in children (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Adjuvant used with local anaesthetic agent in caudal is more effective for post operative analgesia in children . Aim and objective: To find out the duration and quality of caudal analgesia in children undergoing genitourinary surgery by combination of bupivacaine and midazolam. Methods: A total number of sixty patients ASA grade I&II were selected randomly as per inclusion & exclusion criteria in two groups. Thirty in each group. In group A, caudal block was given by bupivacainemidazolam mixture and in group B, caudal block was given by bupivacaine in lateral decubitus position, just after completion of surgery before reversed from GA. In post operative period arterial blood pressure, heart rate, and duration of analgesia were recorded. Results: There was no significant difference between the groups of blood pressure, heart rate, and pain score up to 30 min but after one hour of post operative period pain scores were significant(p